The hands that cradle: A pilot study of parent adverse childhood experience scores. Issue 6 (5th June 2019) - Haltom, John Patrick; Card, Elizabeth; Wells, Nancy; Lowen, Deborah E.
Abstract : ABSTRACT: The purpose of this study was to gather population-specific data within a pediatric hospital and contribute to understanding the intergenerational continuity of adverse childhood experiences (ACEs). This descriptive study aimed at measuring the ACE scores of parents or caretakers whose child was a suspected victim of abuse or neglect. The "Finding Your ACE Score questionnaire was used to determine participants' scores." Fifteen participants enrolled in the study ( N = 15), and 86.7% had exposure to ACEs. Statistical significance was found when comparing ACE scores with reported income levels ( p = .051). This study supports previous findings of ACEs being present in a variety of populations, and it presents practice implications for advance practice registered nurses (APRNs) in various practice settings. Findings support that research regarding how to assess and treat ACEs throughout family members is both necessary and difficult. Additional data regarding the intergenerational continuity of ACEs might influence how APRNs deliver family-specific assessment, treatment, and prevention of ACEs throughout generations of family members.